Novel HPLC-UV method for simultaneous determination of fat-soluble vitamins and coenzyme Q10 in medicines and supplements - Temova Rakuša, Zhane (Acta chimica slovenica, 2017)
A precise, accurate and rapid HPLC-UV method for simultaneous determination of fat-soluble vitamins (vitamin D3, E-acetate, K1, %-carotene, A-palmitate) and coenzyme Q10 was developed and validated according to ICH guidelines. Optimal chromatographic separation of the analytes in minimal analysis time (8 min) was achieved on a Luna C18 150 % 4.6 mm column using a mixture of acetonitrile, tetrahydrofuran and water (50:45:5, v/v/v). The described reversed phase HPLC method is the first published for quantification of these five fat-soluble vitamins and coenzyme Q10 within a single chromatographic run. The method was further applied for quantification of the analytes in selected liquid and solid dosage forms, registered as nutritional supplements and prescription medicines, which confirmed its suitability for routine analysis.
Keywords: chemistry; farmacevtske oblike; HPLC-UV metoda; koencim Q10; lipofilni vitamini